Analisis Pasar Modal Syariah 5 Negara Asean di Era Pandemi COVID 19: (Analysis of Sharia Capital Markets in5 ASEANCountries in The Eraof TheCovid-19Pandemic) - Muhammad Ryan Romadhon; Misnen Ardiansyah (UPT Penerbitan Universitas Jember, 2022)
One of the efforts made to measure the stability of the economy in a country is by looking at the performance of its stock market. The stock market can be said to have a good performance, if it is able to reflect prices that are relevant to the news that is developing in the community. The purpose of this study was to examine the influence of the Islamic capital market in 5 ASEAN countries in the era of the Covid-19. This study uses a quantitative approach with daily data in 2020 as the database. The analysis model uses panel data regression with the Common Effect Model (CEM). The results showed that the Singapore, Philippines, and Thailand sharia stock indexes had a significant positive effect on the Indonesian sharia stock index, while the Malaysian sharia stock index had a significant negative effect on Indonesiaan sharia stock index in the era of the Covid-19 Pandemic.